Culioli, Adamczewski et la linguistique anglaise - Ariel Laurencio Tacoronte (Anglophonia)
In his research on the analysis of languages, Culioli (1968, 1971) states that it is essential to build a system of representation with formal properties in order to be able to perform a calculus in linguistics. We will try here to identify the basis of Culioli’s theoretical formalization which allowed Adamczewski (1978) to construct his metaoperational grammar of English, a grammar consisting of principles later established by this author as universal, starting from the English be + ing structure. In line with the formalization in linguistics as stated by Culioli, we have incorporated other principles and tools into Adamczewski’s model, such as the part / whole principle or the inference generation principle. This has allowed us to determine other characteristics of this structure, such as its ability to refer to past events, even when conjugated in present tense. This integrated model, built along Culiolian formalization parameters, allows us not only to analyze and better understand the enunciative functioning of the structure, or its equivalents in other languages, such as in French être en train de, but also to sketch, still within the enunciative framework, a new hypothesis on the possible metaphorical motivation of the latter.